Additional New Cytotoxic Triquinane-Type Sesquiterpenoids Chondrosterins K–M from the Marine Fungus Chondrostereum sp. - Lei Huang; Wen-Jian Lan; Rong Deng; Gong-Kan Feng; Qing-Yan Xu; Zhi-Yu Hu; Xiao-Feng Zhu; Hou-Jin Li (Marine Drugs, 2016)
By the method of 1H NMR prescreening and tracing the diagnostic proton signals of the methyl groups, three additional new triquinane-type sesquiterpenoids—chondrosterins K–M (1–3) and the known sesquiterpenoid anhydroarthrosporone (4)—were isolated from the marine fungus Chondrostereum sp. Their structures were elucidated on the basis of MS, 1D, and 2D NMR data. Chondrosterin K is a rare hirsutane sesquiterpenoid, in which a methyl group was migrated from C-2 to C-6 and has a double bond between C-2 and C-3. Compounds 1–3 showed significant cytotoxicities against various cancer cell lines in vitro.